Spy kids - Rodriguez, Robert, (Robert Anthony), 1968-; Banderas, Antonio; Gugino, Carla, 1971-; Cumming, Alan, 1965-; Marin, Cheech; Hatcher, Teri.; Trejo, Danny; Shalhoub, Tony, 1953-; Dimension Films (1990- ); Dimension Home Video (Firm); Buena Vista Home Video (Firm) ([Burbank, CA] : Dimension Home Video : Distributed by Buena Vista Home Video, 2001)
Nine years ago, top international spies Gregorio and Ingrid Cortez traded the excitement of espionage for the adventure of parenthood. But when they are called out on a secret mission, the Cortezes are separated from their family and kidnapped by the evil Fegan Floop. Fortunately, there are two people who possess the skills and know-how to reunite the family-- the kids!
Director of photography, Guillermo Navarro ; producers, Elizabeth Avellan, Robert Rodriguez; written and directed by Robert Rodriguez.
Antonio Banderas, Carla Gugino, Alan Cumming, Cheech Marin, Teri Hatcher, Danny Trejo, Tony Shalhoub.
Rated PG.
VHS.
Closed-captioned.
Keywords: Films for the hearing impaired; Children's films; Feature films; Spy films